2022
DOI: 10.1021/acsami.1c19546
|View full text |Cite
|
Sign up to set email alerts
|

Thiocyanate-Passivated Diaminonaphthalene-Incorporated Dion–Jacobson Perovskite for Highly Efficient and Stable Solar Cells

Abstract: Two-dimensional (2D) metal halide perovskites have recently emerged as promising photovoltaic materials due to their superior ambient stability and rich structural diversity. However, power conversion efficiencies (PCEs) of the 2D perovskites solar cells (PSCs) still lag behind their three-dimensional (3D) counterpart, particularly due to the anisotropy in the charge carrier mobility and inhomogeneous energy landscape. A promising alternative is Dion−Jacobson (D−J) phase quasi-2D perovskite, where the bulky or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…The average carrier decay lifetime is 3.02 ns. The narrow FWHM (in PL spectrum) and short average carrier lifetime suggest a strong probability for excitonic carrier recombination and reduced trap-assisted nonradiative recombination. , …”
Section: Resultsmentioning
confidence: 99%
“…The average carrier decay lifetime is 3.02 ns. The narrow FWHM (in PL spectrum) and short average carrier lifetime suggest a strong probability for excitonic carrier recombination and reduced trap-assisted nonradiative recombination. , …”
Section: Resultsmentioning
confidence: 99%
“…Additive engineering has been proven as an established protocol to improve perovskite film uniformity, crystallinity, compactness, and also to minimize the defect states. , Here, to further improve the photovoltaic efficiency of selected n = 4 phase (XDA)­(MA) 3 (Pb) 4 (I) 13 perovskite active layer, NH 4 SCN passivation was done by adding it directly into the perovskite precursor solution. The detailed scheme for precursor solution of NH 4 SCN additive-assisted (XDA)­(MA) 3 (Pb) 4 (I) 13 perovskite is included in the experimental section . The (XDA)­(MA) 3 (Pb) 4 (I) 13 perovskite with different amounts of NH 4 SCN were fabricated with the molar ratio of XDA/MAI/PbI 2 /HI/NH 4 SCN = 1:3:4:2: x .…”
Section: Resultsmentioning
confidence: 99%
“…The MASCN additive-assisted PSCs achieved the maximum PCE of 16.25% and maintain superior ambient stability (35 days) in 45% humidity exposure . Recently, our group has shown that 1,5-diamino naphthalene (NDA) organic cation incorporated 2D D-J phase perovskite with NH 4 SCN treatment can lead to PCE of 15% with high moisture stability …”
Section: Introductionmentioning
confidence: 99%
“…Almost all of these works have predominately focused on stability enhancement while keeping PCE high by using different organic spacers. Another alternative approach to improve the stability and PCE was pursued by using different surface engineering techniques like cross-linking additives, additive engineering, interface defect engineering, etc. Among these techniques, additive engineering is one of the most widely employed method which enhances the carrier transport and reduces nonradiative recombination. Various additives such as ammonium chloride (NH 4 Cl), methylammonium chloride (MACl), lead thiocyanate (PbSCN), ammonium thiocyanate (NH 4 SCN), and methylammonium thiocyanate (MASCN) have been utilized for this purpose. However, a collective effect of incorporating 2D perovskite along with additional passivation engineering on 3D perovskite is almost not explored.…”
Section: Introductionmentioning
confidence: 99%